2016
DOI: 10.1093/her/cyw033
|View full text |Cite
|
Sign up to set email alerts
|

Participation levels in 25 Community-based participatory research projects

Abstract: This analysis describes the nature of community participation in National Institutes of Health and Centers for Disease Control and Prevention funded community-based participatory research (CBPR) projects, and explores the scientific and social implications of variation in community participation. We conducted in-depth interviews in 2012 with professional and community researchers from 25 CBPR projects in the Southeast US. Interview topics focused on participants' experiences with the nature and conduct of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…We propose a research apprentice model of peer research engagement that would add a deliberate dimension of workforce development to the publicly funded research enterprise while contributing to realize the goals of capacity building, empowerment, and co-learning intrinsic to participatory and translational research(6,18–22). As envisioned, the model capitalizes on the widespread engagement practice of providing community members with training in core concepts, basic research methods, and miscellaneous job skills(5,9,20,23,24), but emphasizes comprehensive instruction to render the apprentice skilled both on broad and specific aspects of research, while fostering aptitudes needed for sustained workforce participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose a research apprentice model of peer research engagement that would add a deliberate dimension of workforce development to the publicly funded research enterprise while contributing to realize the goals of capacity building, empowerment, and co-learning intrinsic to participatory and translational research(6,18–22). As envisioned, the model capitalizes on the widespread engagement practice of providing community members with training in core concepts, basic research methods, and miscellaneous job skills(5,9,20,23,24), but emphasizes comprehensive instruction to render the apprentice skilled both on broad and specific aspects of research, while fostering aptitudes needed for sustained workforce participation.…”
Section: Discussionmentioning
confidence: 99%
“…Both rely on training and mentoring of peer researchers to promote their understanding of research and proficiency in study tasks(9). However, while the employment model includes capacity building as a by-product,(5,9,18,20,24) the apprenticeship model has capacity building as its main goal.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond translational models, Community-Based Participatory Research [4] or Action Research [5] are alternate practices involving multiple stakeholders; however, there is generally no requirement for a collaborative commitment throughout the whole process from the design phase, and there are often power dynamics that remain unresolved. The result can be that the researchers drive the initial concepts and then leave post intervention trial, taking the knowledge gained with them [6], thus limiting ongoing benefit to those for whom the intervention was being designed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the popularity of these definitions of CBPR, other scholars employ the term to describe a much broader array of translation-focused, partnership approaches to research [1,14,15]. Indeed, Spears Johnson et al [16] revealed that, of 25 CBPR health projects funded by the Centers for Disease Control and NIH, community involvement ranged from 2 out of 13 defined phases of the research project to all 13. While some studies reflected Israel and colleagues' [8] definition of CBPR and demonstrated high levels of non-academic partner authority throughout the project, others involved community partners in only the participant recruitment or dissemination of the results phases.…”
Section: Introductionmentioning
confidence: 99%